Maternal supply of methionine during late-pregnancy enhances rate of Holstein calf development in utero and postnatal growth to a greater extent than colostrum source. Issue 1 (December 2018) - Alharthi, Abdulrahman; Batistel, Fernanda; Abdelmegeid, Mohamed; Lascano, Gustavo; Parys, Claudia; Helmbrecht, Ariane; Trevisi, Erminio; Loor, Juan
Abstract Background Pregnancy and early life are critical periods of plasticity during which the fetus and neonate may be influenced by environmental factors such as nutrition. Maternal methionine (Met) supply in non-ruminants during pregnancy can affect offspring development and growth. Thus, the objective of this study was to investigate if increasing Met supply during late-pregnancy affects developmental parameters of the calf at birth and if either maternal Met or colostrum from Met-fed cows alters calf growth. Calves born to Holstein cows individually-fed a basal control [CON; 1.47 Mcal/kg dry matter (DM) and 15.3% crude protein] diet with no added Met or CON plus ethylcellulose rumen-protected Met (MET; Mepron® at 0.09% of diet DM; Evonik Nutrition & Care GmbH, Germany) during the last 28 ± 2 d of pregnancy were used. A total of 39 calves were in CON (n = 22 bulls, 17 heifers) and 42 in MET (n = 20 bulls, 22 heifers). At birth, calves were randomly allocated considering dam treatment and colostrum as follows: 1) calves from CON cows and colostrum from CON cows (n = 21); 2) calves from CON cows and colostrum from MET cows (n = 18); 3) calves from MET cows and colostrum from MET cows (n = 22); and 4) calves from MET cows and colostrum from CON cows (n = 20). All calves were housed, managed, and fed individually during the first 9 wk of life. Results Despite greater daily DM intake pre-partum in cows fed MET (15.7 vs. 14.4 ± 0.12 kg/d, P < 0.05), colostrum quality and quantity were not affected by maternal diet. At birth, MET calves had greater (P ≤ 0.05) body weight (BW, 44.1 vs. 42.1 ± 0.70 kg), hip height (HH, 81.3 vs. 79.6 ± 0.53 cm) and wither height (WH, 77.8 vs. 75.9 ± 0.47 cm). In contrast, concentrations of His, Lys, and Asn in plasma were lower (P ≤ 0.05) in MET calves. Regardless of colostrum source, the greater BW, HH, and WH in MET calves at birth persisted through 9 wk of age resulting in average responses of + 3.1 kg BW, + 1.9 cm HH, and + 1.8 cm WH compared with CON. Average daily gain during the 9 wk was (P < 0.05) 0.72 ± 0.02 kg/d in MET compared with 0.67 ± 0.02 kg/d in CON calves. Respiratory scores were normal and did not differ (P > 0.05) due to maternal Met supply or colostrum source. However, fecal scores tended to be lower (P ≤ 0.10) in MET calves regardless of colostrum source. Conclusions Increasing the maternal supply of MET during late-pregnancy enhanced growth in utero as well as during the pre-weaning and early post-weaning periods. Although the 1 kg/d greater DM intake during the last 2–3 wk prior to parturition could explain a portion of the 2 kg extra body mass of MET calves at birth, other mechanisms potentially encompassing nutrient assimilation efficiency likely played a role. Assessing the exact mechanisms sensitive to supply of Met or total amino acid supply during the latter stages of growth in utero merit further research.